1994
DOI: 10.1039/p29940002301
|View full text |Cite
|
Sign up to set email alerts
|

Metal-ion-promoted hydrolysis of polyuridylic acid

Abstract: First-order rate constants for the hydrolysis of polyuridylic acid in the absence and presence of various metal ions and their chelates have been determined under neutral and slightly acidic conditions. The hydrolysis has been shown to proceed by cleavage of non-terminal bonds rather than by stepwise release of monomeric nucleotides. Only the hydrolysis of the 3',5'-phosphodiester bonds is accelerated by metal ions, not their isomerization to 2',5'-bonds. The catalytically active species has been shown to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 41 publications
3
48
1
Order By: Relevance
“…Here we found that Zn 2þ catalysis was quite effective in all cases, but diminished by the additional polymers. The binding of Zn 2þ with strong ligands, such as the nitrogen on the polyethylenimine backbone or imidazoles, apparently decreased its Lewis acidity and, therefore, its catalytic activity (9,31).…”
Section: Resultsmentioning
confidence: 99%
“…Here we found that Zn 2þ catalysis was quite effective in all cases, but diminished by the additional polymers. The binding of Zn 2þ with strong ligands, such as the nitrogen on the polyethylenimine backbone or imidazoles, apparently decreased its Lewis acidity and, therefore, its catalytic activity (9,31).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the pK a s of the aqua complexes of Cd 2+ , Ni 2+ , Co 2+ , Pb 2+ , and Zn 2+ fall within the 7-10 range (31). This fact may contribute to the previously observed nonspecific Zn 2+ -dependent hydrolysis of RNA (32)(33)(34). Third, the geometric requirements of the binding site place a limitation on the size of the bound metal ion.…”
Section: +mentioning
confidence: 99%
“…All these rate profiles exhibit a marked rate acceleration in the pH range 6.5 ± 7.0 (at 908) and a broad rate maximum at pH 7.0 ± 7. [21]. The retardation observed at pH > 7.5 may be attributed to precipitation of the metal ions as a hydroxo complex.…”
mentioning
confidence: 93%
“…The rate-accelerating effect of the mononuclear 2 complex is equal to that of the Zn 2 complex of 1,5,9-triazacyclododecane [20] [21]. In all likelihood, the metal ion in 2 is bound to only one of the azacrown moieties, the other one having no effect on the course of the reaction.…”
mentioning
confidence: 97%